2015
DOI: 10.1002/ab.21610
|View full text |Cite
|
Sign up to set email alerts
|

Reducing cyberbullying: A theory of reasoned action‐based video prevention program for college students

Abstract: Few studies have evaluated the effectiveness of cyberbullying prevention/intervention programs. The goals of the present study were to develop a Theory of Reasoned Action (TRA)-based video program to increase cyberbullying knowledge (1) and empathy toward cyberbullying victims (2), reduce favorable attitudes toward cyberbullying (3), decrease positive injunctive (4) and descriptive norms about cyberbullying (5), and reduce cyberbullying intentions (6) and cyberbullying behavior (7). One hundred sixty-seven col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 73 publications
(68 reference statements)
1
40
1
5
Order By: Relevance
“…() in accordance with guidelines proposed by Ajzen and Fishbein (), asking students to rate their assumptions about how many significant others (e.g., closest friends, classmates, people of their age) perform or condone cyberbullying on a 5‐point‐scale (1 = none of them to 5 = almost all of them/all of them ). Previous cyberbullying‐related studies that used similar (Doane et al., ; Heirman & Walrave, ) or identical scales (Lazuras et al., ), demonstrated the validity of this instrument in this context. In the current study, the internal consistency was α = .70 at the first measurement occasion and α = .66 at the second measurement occasion.…”
Section: Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…() in accordance with guidelines proposed by Ajzen and Fishbein (), asking students to rate their assumptions about how many significant others (e.g., closest friends, classmates, people of their age) perform or condone cyberbullying on a 5‐point‐scale (1 = none of them to 5 = almost all of them/all of them ). Previous cyberbullying‐related studies that used similar (Doane et al., ; Heirman & Walrave, ) or identical scales (Lazuras et al., ), demonstrated the validity of this instrument in this context. In the current study, the internal consistency was α = .70 at the first measurement occasion and α = .66 at the second measurement occasion.…”
Section: Methodsmentioning
confidence: 70%
“…There are a large number of studies applying the same semantic differentials, supporting the reliability and predictive validity of the instrument for assessing attitudes related to health behaviors. Similarly, recent studies have demonstrated the appropriateness of the measure for the assessment of attitudes toward cyberbullying (e.g., Doane et al., ; Heirman & Walrave, ; Lazuras et al., ). In the present study, the internal consistency was α = .81 at the first measurement occasion and α = .88 at the second measurement occasion.…”
Section: Methodsmentioning
confidence: 89%
“…Las primeras evaluaciones de otros programas para la atención de cyberbullying (Chibnall, Wallace, Leitch y Lunhofer, 2006;Doane, 2011;Doane et al, 2016;Lee et al, 2013) impactaron solo en algunos de los indicadores que consideraron. Se retomó el caso del Brief Internet Cyberbullying Prevention Program, que ha realizado dos evaluaciones sobre su efi cacia, la primera de ellas (Doane, 2011) detectó un aumento de conocimiento del fenómeno y disminución de perpetración y actitudes favorecedoras de cyberbullying, pero no evidenció mejora en la empatía hacia las víctimas; posteriormente se revisó y probó el programa (Doane et al, 2016) y se confi rmó la mejora en los tres indicadores que ya había detectado la primera evaluación, además de que se incrementó la empatía hacia las víctimas.…”
Section: Discussionunclassified
“…Tal es el caso de los programas como Let's Fight It Together: What We All Can Do to Prevent Cyberbullying (Childnet, 2007), que recurre a videos cortos; Cyber Bullying: A Prevention Curriculum (Kowalski y Agatston, 2008), que consta de ocho sesiones; Brief Internet Cyberbullying Prevention Program (Doane, 2011;Doane et al, 2016), un programa breve en formato de video y las Webquest (Lee et al, 2013) desarrolladas en ocho sesiones de 45 minutos cada una.…”
Section: Discussionunclassified
See 1 more Smart Citation